A critical review of cold-formed steel seismic resistant systems: Recent developments, challenges and future directions. (November 2022) - Hasanali, Maryam; Roy, Krishanu; Mojtabaei, Seyed Mohammad; Hajirasouliha, Iman; Clifton, G. Charles; Lim, James B.P.
Abstract: Cold-formed steel (CFS) systems have seen an increased application in the past few decades, especially in the construction of low- to mid-rise buildings. CFS members offer considerable structural and environmental advantages, such as low weight, ease and speed of construction, greater manufacturing flexibility, recyclability and low embodied carbon. Despite the significant potential offered by CFS structural systems, the seismic design of lateral force-resisting systems (LFRS) for CFS multi-story buildings is challenging. There are many different types of systems capable of providing the lateral load resistance capacity of the CFS framing, and this paper provides a comprehensive review of the research developments made in CFS braced-wall systems and moment-resisting frames, as the most conventional systems, to study their structural performance and identify the research gaps, challenges, and future directions. The major research developments are summarised in terms of load capacity, stiffness, energy dissipation capacity and failure mode. As an outcome of the crucial review, it was found that CFS LFRSs can generally offer more efficient design solutions regarding seismic characteristics such as high ductility and energy dissipation capacity. Despite a rather large body of research on CFS braced walls, it is necessary to assess the response of these systems in various aspects, such as developing an optimisation framework to withstand the combination of vertical and horizontal loading plus resist the impact of severe fire. With respect to moment-resisting frames, one of the main research needs is to develop systems suitable for multi-story buildings, especially in seismic regions. Highlights: Summarising research developments made in cold-formed steel braced-wall systems and moment-resisting frames. The structural performance challenges of these systems are identified. The effects of the key design parameters on the structural performance of these systems are concluded. Knowledge gaps are identified for future directions. Research highlights for improving the lateral performance of these systems are classified.